A comparison of 30‐day surgical outcomes for minimally invasive and open sacrocolpopexy. Issue 2 (22nd November 2013) - Tyson, Mark D.; Wolter, Christopher E.
<x xml:space="preserve">Abstract</x> Aims Minimally invasive sacrocolpopexy (MISC) has gained widespread acceptance without randomized or population‐based data to support its use. This study compares 30‐day outcomes after MISC and open sacrocolpopexy (OSC) using population‐based data. Methods The National Surgical Quality Improvement Program (NSQIP) database was used to acquire 1, 786 sacrocolpopexy operations (659 OSC and 1, 127 MISC) performed from 2005 to 2011. A propensity‐weighted comparative analysis of perioperative morbidity was performed. Results Among women undergoing sacrocolpopexy, the proportion of MISC procedures increased from 7.1% in 2006 to 68.8% in 2011. Women undergoing OSC were older (P < 0.001) and had somewhat higher American Society of Anesthesiologists classifications (P = 0.11). Unadjusted comparisons between groups revealed higher rates of superficial (P < 0.001) and deep surgical (P = 0.009) site infections in the OSC group. There was also a higher rate of blood transfusions (P = 0.02), a longer length of hospitalization (P < 0.001), and a shorter operative time (P < 0.001) among patients undergoing OSC. In the propensity‐weighted analysis, MISC was associated with lower rates of wound infections (1.1% vs. 3.0%; P = 0.01), lower blood transfusion rates (0.7% vs. 2.3%; P = 0.01), a shorter mean hospitalization (1.4 vs. 3.0 days; P < 0.001), and a longer mean operative time (224.8 vs. 188.6 min; P < 0.001). No differences were noted among renal, infectious, or neurologic complications, although pulmonary complications were higher in the OSC group (0.3% vs. 1.0%; P = 0.08). No differences in 30‐day mortality were noted (0.1% vs. 0.2%; P = 0.61). Conclusions MISC was associated with lower perioperative morbidity in this propensity‐weighted analysis. Neurourol. Urodynam. 34:151–155, 2015. © 2013 Wiley Periodicals, Inc.